2021
DOI: 10.1080/13880209.2020.1870506
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-inflammatory and antioxidant pharmcodynamic compoents of naoxintong capsules as a basis of broad spectrum effects

Abstract: Context: Naoxintong capsule (NXT) is one of the most prevalent Traditional Chinese Medicine formulations in the treatment of coronary heart disease (CHD), yet the action of pharmacodynamic components remains unclear.Objective: To determine the basis by which pharmacodynamic components ofNXT may be effective in the treatment of CHD. Materials and methods: The protective effect of NXT (0.01-100 lg/mL) on 293 T and hy926 cells was determined by MTT assay for 24 h. Afterwards, to investigate the pharmacodynamic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The PI3K/Akt signal cascade is crucial in triggering and amplifying the cytokine network [ 38 ]. The PI3K/AKT signaling pathway is believed to play an important role in various diseases, including cancer, cardiovascular diseases, and inflammation [ 39 ]. Akt activation resulted in NF-κB activation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signal cascade is crucial in triggering and amplifying the cytokine network [ 38 ]. The PI3K/AKT signaling pathway is believed to play an important role in various diseases, including cancer, cardiovascular diseases, and inflammation [ 39 ]. Akt activation resulted in NF-κB activation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that inflammatory responses are pivotal in precipitating cardiovascular events in patients diagnosed with CHD ( Haybar et al, 2019 ). NXT can suppress intra-arterial inflammatory responses, thereby reducing serum levels of inflammatory markers such as TNF-α, IL-6, IL-18, monocyte chemoattractant protein 1 (MCP-1) ( Luo and Liao, 2019 ), and metalloproteinase 9 ( Lv et al, 2021 ). This reduction in inflammatory indicators contributes to a decrease in the incidence of adverse cardiovascular events in patients, thereby enhancing their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the clinical use of choline enzyme inhibitors and antioxidant drugs for treatment, but the effect is not ideal. Studies have shown that the NXTC inhibits nerve cell apoptosis and protects nerve function, while it promotes cerebrovascular dilation, improves blood supply to the brain, regulates microcirculation, promotes oxygen delivery, and relieves hypoxia, thereby improving nerve function in patients [14] . In addition, the tanshinone component contained in the drug has the effects of antagonizing the proliferation of glial cells and reducing the damage of nerve function [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the NXTC inhibits nerve cell apoptosis and protects nerve function, while it promotes cerebrovascular dilation, improves blood supply to the brain, regulates microcirculation, promotes oxygen delivery, and relieves hypoxia, thereby improving nerve function in patients. [14] In addition, the tanshinone component contained in the drug has the effects of antagonizing the proliferation of glial cells and reducing the damage of nerve function. [15] Although NXTC have been widely used by clinicians in the treatment of VaD, its effectiveness and safety are still controversial.…”
Section: Discussionmentioning
confidence: 99%